A Journey of Healing from Addiction: One Person's Story. Issue 2 (3rd April 2017) - Gee, Rose Mary; Rushing, Alison; Talley, Brenda; Dubert, Christy J.; Hamilton, Ellen K.; Worrell-Carlisle, Pamela
ABSTRACT: Recovery from addiction to alcohol/drugs is more often than not presented in the literature in an almost exclusively clinicalized version, and the voices of those who suffer from this disease are never heard. This story seeks to present one person's voice as she tells of her journey from addiction to recovery and serenity. The story emanates from a larger study that focused on a particular methodological format—one that sought to embody the wholeness of the person rather than portray a fractured description of reality. This article shares one person's story of her experience represented in an aesthetic format.